Animistic Narratology in the Purung Ta Liang Marapu Ritual in Central Sumba, East Nusa Tenggara Indonesia (Study: Narraethnography) - Dota, Nonrila Haba; Simanjuntak, Nensy Megawati; Tobing, Victor MTL; Wardhani, Widya Desary Setia (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Tradition and culture in Indonesia are deeply connected, particularly through rituals and belief systems. The Purung Ta Liang Marapu ritual in East Sumba, NTT, is a sacred ceremony conducted annually to worship deities, involving offerings of animals and betel leaves on sacred objects. This ritual embodies animism, the belief in spiritual forces behind natural phenomena, which are personified as spirits or gods. The aim of this study is to explore the animistic narratology within the Purung Ta Liang Marapu ritual using a narraethnographic approach, a method that combines narrative and ethnography to systematically explain cultural values and traditions. The research highlights that access to the ritual's spiritual power is reserved for specific individuals, such as kings or priests, who play a central role in maintaining these cultural practices. This study contributes to the understanding of how animism shapes and sustains traditional rituals in Central Sumba, providing a deeper insight into the preservation of indigenous belief systems.